CARDIAC SURGERYTrends in mechanical aortic valve replacement surgery in a large, multi-surgeon, single hospital practice - Kalender, Mehmet; Fedakar, Ali; Adademir, Taylan; Salihi, Salih; Boyacıoğlu, Kamil; Özbek, Babürhan; Taşar, Mehmet; Balkanay, Mehmet (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
Introduction: In recent decades, new high-performance prostheses have been invented for use with small aortic annuli, and they have helped avoid patient prosthesis mismatch (PPM) without the need for aortic annular enlargement. The purpose of this study is to examine the trends in mechanical aortic valve replacement surgery in a large, multi-surgeon, single hospital practice. Material and methods: Between January 1999 and January 2008, 1337 consecutive patients underwent aortic valve replacement (AVR) with or without concomitant aortic annulus enlargement. Patients with aortic dissections and patients undergoing Bentall and Ross procedures were excluded from the analysis. Patients were grouped according to the used aortic valve size. The data were collected and analyzed retrospectively. Results : The mean age of the subjects was 54.37 ± 17.35 (range: 10-84), and 881 of them were men (65.8%). The number of aortic root enlargement procedures decreased over the years (p < 0.05); particularly, the decline of the Nicks procedures was statistically significant (p < 0.05). In 2008, the most frequently used valve size was 23, which stands in contrast with the smaller size preferred in 1999 (p 0.05). Although the use of combined surgery increased in time, there was no statistical relationship with any increase in mortality rates (p > 0.05). Conclusions : This study showed that avoiding the procedure of aortic root enlargement and implanting high-performance prostheses with larger valves is safe.